Al-Sadir McIntyre’s Communitarianistic Confrontation with the Liberal State of the Modern Age - Tahmaseb Alipouriani; Mokhtar Nouri (دولت‌پژوهی, 2019)
The institution of the modern state, based on the liberal doctrine of social contract, has been questioned in the age of globalization by the formation of paradigmatic transformations of political thought from different think tanks. This kind of criticism of liberal discourse encompasses a range of critical thinkers such as Michel Foucault, Jacques Derrida Giorgo Agamben, Jacques Rancière and others. But the critique of the state by contemporary thinkers is not confined to this category of thinkers, but communitarianism, with its thinkers such as Al-Sadir McIntyre, can be regarded as one of these critical schools of thought in the paradigm of contemporary political philosophy with a critical look at the most important liberal propositions of modern times such as individualism, state neutrality, universality of this kind of thinking and an emphasis on concepts such as communitarianism, virtue, state moral interventionism, and contextualization. The focus of this article will be to examine McIntyre's critical attitude towards the issue of "state neutrality." The question is, "What is Al-Sadir McIntyre's view of the institution of government? And what is his position on the neutrality of the state in liberal thought? "It is assumed that “First of all, McIntyre has no endorsing view of modern government and its grand narrative, and is in favor of communism. It also denies the impartiality of the state in liberal thought and advocates the rule-based interventionism of the state to moralize citizens ". Macintyre is a new Aristotelian thinker who emphasizes the restoration of virtue and prosperity in the modern age as it was in the classical Greek era.